Embattled River : The Hudson and Modern American Environmentalism - Schuyler, David (Book collections on Project MUSE., 2018)
"Analyzes the ways in which the Hudson River has become a key battleground in the emergence of modern environmentalism in the United States since Consolidated Edison announced plans to construct a pumped storage power plant at Storm King Mountain in 1962"--Provided by publisher.